Maternal allocation in eggs when counting on helpers in a cooperatively breeding bird - Valencia-Ruíz, Juliána; Mateos, Concha; de la Cruz, Carlos; Carranza, Juan (Nordic Society Oikos, 2016)
For cooperatively breeding birds, it has been proposed that breeders should reduce their investment in eggs when they count on helpers, because this can be compensated for by helpers provisioning of nestlings. Data from some species have supported this prediction, but this is not the case in others. It has also been proposed that mothers should not reduce but rather increase investment if the presence of helpers enhances the reproductive value of offspring, a pattern that might also influence egg production as long as helpers are predictable for laying females. Here, we studied maternal expenditure in eggs and clutches in the Iberian magpie, to see whether mothers reduce their expenditure at the egg stage in the presence of helpers. Our results show that investment in clutches varied depending on the year, date in the season and age of the mother, but there were no reductions in maternal expenditure per individual egg when they counted on helpers. On the contrary, a pattern emerged in the opposite direction of more investment in eggs associated with the future presence of helpers at the nestling stage. Our data suggest that the predictability of helpers, along with the type of benefits accrued from the contribution of helpers, may be crucial to understanding the reaction of mothers at egg production.
Keywords: Huevos - Incubación; Maternal allocation; eggs; Cooperative breeding